Strategi Pengembangan Usaha Wisata Desa Melalui Pemberdayaan Masyarakat Desa (Studi Kasus Wisata Bunga Anggrek Tondok Bakaru Kecamatan Mamasa Kabupaten Mamasa) - Amelia Amelia; Chuduriah Sahabuddin; Nur Fitrah (Universitas Medan Area, 2021)
This research is a qualitative research with a descriptive approach which aims to determine the Strategy of Village Tourism Business Development Through Village Community Empowerment. Data collection was carried out through observation, interviews, and documentation techniques. The data analysis technique used is qualitative data analysis, which describes and interprets the data obtained in the field from key informants. As for the research results from this title, namely the strategy of developing village tourism businesses (flower orchids) through empowering rural communities by utilizing natural resources. existing resources such as empowering seeds through tissue culture, namely the development of orchids by cultivating their seeds and obtaining goods in collaboration with the orchid supplying community, the second strategy is sustainable socialization of orchid plants to the community in the tondok Bakaru itself and the community providing orchid plants ( people who take orchids in the forest), the third strategy is cooperation with bumdes.